2015
DOI: 10.1136/jmedgenet-2015-103239
|View full text |Cite
|
Sign up to set email alerts
|

Hypomyelination and developmental delay associated withVPS11mutation in Ashkenazi-Jewish patients

Abstract: We speculate that in neuronal cells, impairment of fusion of the late endosome to the vacuole would attenuate the degradation of plasma membrane receptors, thereby underlying the progressive neuronal phenotype in our patients. The VPS11 p.Cys846Gly mutation should be added to the AJ carrier screening panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
(16 reference statements)
5
41
1
Order By: Relevance
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
“…(75)(76)(77). These observations are of particular importance with regards to the design of a possible treatment of HOPS related disorders (69,70,73,78,79).…”
Section: Discussionmentioning
confidence: 89%
“…Mutations in CHEVI or HOPS components commonly cause neurological defects in the C. elegans, D. melanogaster, zebrafish and mice animal models (Fernandes et al, 2014;Harrington et al, 2012;Kim et al, 2004;Peng et al, 2012b;Suzuki et al, 2003;Zhang et al, 2016). Patients carrying mutations in the core components Vps11, Vps16 or Vps33A (Cai et al, 2016;Edvardson et al, 2015;Hörtnagel et al, 2016;Kondo et al, 2017;Zhang et al, 2016) or ARC-causing mutations in the CHEVI subunits also show neurological symptoms (Eastham et al, 2001). Intriguingly, mutations in Vps3 or Vps8 seemingly do not impact neuronal function (Lorincz et al, 2016).…”
Section: Neurological Defectsmentioning
confidence: 99%
“…Affected HLD12 patients manifest severely delayed or even lack of psychomotor development, acquired microcephaly, lack of speech, and often lack of spontaneous movement due to hypotonia and spasticity. Brain MRI shows hypomyelination and thin corpus callosum (46).…”
Section: Hypomyelinating Leukodystrophy 12 (Vps11 Related Disorder -Hmentioning
confidence: 99%